2016
DOI: 10.1108/jeim-03-2014-0034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parent-subsidiary conflict on ERP implementation

Abstract: Purpose – In spite of the large body of literature on success factors of enterprise resource planning (ERP) implementation, there is a need to explore its multinational dimension. The purpose of this paper is to explore the impact of the conflict between parent and subsidiary on the process of ERP implementation in a multinational enterprise (MNE). Design/methodology/approach – Using an interpretive case study methodology, this paper ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 76 publications
0
8
0
5
Order By: Relevance
“…They investigated enabling factors for top management support and showed that end users believe organizational communication and training have a positive effect on top management support. Gavidia (2016) shows that managing parent–subsidiary conflict is a CSF for ERP implementation.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…They investigated enabling factors for top management support and showed that end users believe organizational communication and training have a positive effect on top management support. Gavidia (2016) shows that managing parent–subsidiary conflict is a CSF for ERP implementation.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Other studies address the importance of the client and the definition of service level agreements (SLAs) for the minimization of conflicts (Heiskanen et al, 2008;Kaipia and Turkulainen, 2017). In scenarios, enterprise resources planning (ERP) implementation Gavidia (2016) identified that conflict is a critical success factor.…”
Section: Sources and Causes Of Ito Conflictsmentioning
confidence: 99%
“…The demand for more heterogeneous steering of foreign subsidiaries in MNC arises from the relationship of the subsidiaries with the parents or headquarters (Birkinshaw and Hood, 1998), particularly in complex matrix or network structures with functional departments, business units and geographic areas which pursue their own goals or interests and are in opposition to the subsidiaries' goals (Gavidia, 2016). This demand has reignited the debate about the headquarter-subsidiary relationship, with fundamental concepts such as hierarchy and coordination and a subsidiary's autonomy (e.g., Gammelgaard et al, 2012).…”
Section: Demand For More Intensely Heterogeneous Steeringmentioning
confidence: 99%
“…First of all, contingency theory considers different environmental conditions at headquarters/parent und subsidiaries (e.g., Doz and Prahalad, 1991;Gavidia, 2016), which have been discussed for a long time now as the global-local -'GLOCAL 'dilemma (Laudien and Freiling, 2011). Although today global integration or standardisation is still necessary to pursue the goal of improving process efficiency and reducing redundancies, there is a growing need for local adaptation enabling greater creative freedom, flexibility and market proximity.…”
Section: Demand For More Intensely Heterogeneous Steeringmentioning
confidence: 99%